Comportamiento de la sexualidad en estudiantes de bachillerato del Colegio Dra. Matilde Hidalgo de Procel, Machala 2010 - Castillo Soto, Gladys C. (2011)
A descriptive study was conducted cross-sectional non-experimental to 83 adolescents of both sexes in the students in the baccalaureate diversified cycle of the college Dra. Matilde Hidalgo de Procel in the city of Machala 2010 – 2011, selected by sampling between the ages of 14-19 years. A survey was administered to each adolescents, where were investigated data from personal identity, age of first sexual intercourse more used in the methods used in them, numbers of sexual partners and contraceptives more used in the subsequent relations, among others.